The relationship between menopausal hormone therapy and keratinocyte carcinoma: A review - R. Suresh; A. Twigg; J.E. Murase (Wolters Kluwer, 2019)
Introduction: Keratinocyte carcinoma (KC) is the most common malignancy in the United States. The two most common forms of KC are basal cell carcinoma and squamous cell carcinoma (SCC), which account for 80% and 20% of cases, respectively. Objective: There are many well-established risk factors for KC, but a more controversial risk factor for KC development is menopausal hormone therapy (MHT). This review synthesizes existing information on this topic and identifies knowledge gaps for future study. Methods: A systematic review of the literature using the Medical Subject Headings terms "menopausal hormone therapy; skin neoplasms" was conducted in the PubMed database from March 19, 2018 to April 1, 2018. This yielded 168 articles, case reports, and reviews, which were further refined for inclusion during the development of this manuscript. Additional articles were identified from cited references. Results: Four studies pertaining to this topic were identified. The results were evaluated in the context of these studies' strengths and weaknesses. MHT contributes to an increased risk of basal cell carcinoma in Caucasian subjects and may make these tumors histologically more aggressive. There is not enough evidence to make a conclusion with regard to a potential relationship between MHT and SCC. However, one study suggested an increased risk of SCC with MHT use and another demonstrated a temporal association with prolonged MHT use and increased risk of SCC development. Conclusion: Ever users of MHT should be screened more frequently for KC. This issue is of importance to dermatologists because patients who receive earlier diagnoses of KC will have a better opportunity to pursue treatment. Keywords: menopausal hormone therapy, skin neoplasm, basal cell carcinoma, squamous cell carcinoma, keratinocyte carcinoma